B(RAIN)2—BRAIN integrated Resource for Anatomy and Intracranial Neurophysiology - Amirreza Alijanpourotaghsara; Koorosh Mirpour; Jeong Woo Choi; Krishna Kanth Chitta; Ahmed Shalaby; Misque Boswell; Sahil Chilukuri; Samantha L. Cohen; Ryan Byon; Mohsen Benam; Saar Kariv; Jeon Lee; et al. (Scientific Data)
Abstract The Brain Integrated Resource for Human Anatomy and Intracranial Neurophysiology (B(RAIN)2) is a multi-center data resource that provides standardized imaging and intracranial neurophysiological data from patients who have undergone deep brain stimulation (DBS) implantation with intracranial electroencephalography (iEEG) recordings. The database includes patients’ electrophysiological recordings from the cerebral cortex and deeper brain structures, alongside high-resolution neurological imaging scans taken at preoperative, intraoperative, and postoperative stages. The data are systematically organized using the Brain Imaging Data Structure (BIDS) format for imaging data and iEEG-BIDS for intracranial electrophysiological recordings. This standardized structure facilitates data integration, sharing, and analysis across research institutions. Additionally, the database features detailed metadata, such as diagnostic information and neurological assessment scores, providing a comprehensive profile of each patient’s data.